Evaluating the impact of smart city construction on sewage treatment in China from a synergistic perspective - Xing Zhang; Xiao Yu; Xuedong Hu (Scientific Reports)
Abstract Urbanization exacerbates the prevalence of urban diseases such as water pollution. Smart city construction (SCC), a prevailing global trend in urban development, has the potential to catalyze the symbiotic development of the urban economy, society, and environment. This study utilized a difference-in-differences (DID) model with panel data from 150 prefecture-level cities in China during the period of 2011–2017 to evaluate the impact of SCC on urban sewage treatment. The results revealed a statistically significant increase in the sewage treatment level, which remained robust even after rigorous tests were performed. The mechanism analysis revealed that SCC can improve the level of sewage treatment through increasing the fiscal self-sufficiency rate (FSR) and industrial upgrading (IU). Furthermore, heterogeneity analysis revealed that in cities with a high level of financial development and public environmental attention (PEA), coupled with a low level of environmental attention from higher-level government, the advancement of the sewage treatment level can be more effectively facilitated through SCC. In conclusion, the promotional effect of SCC on the sewage treatment level is influenced by a combination of technological, economic, political, and social factors. Therefore, SCC should prioritize the synergistic integration of technological innovations and non-technological factors.